2002
DOI: 10.1007/s11746-002-0604-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing conditions on microstructure of milk fat fraction/sunflower oil blends

Abstract: The effect of processing conditions on the crystallization of blends of a high-melting milk fat fraction and sunflower oil was investigated. Two cooling rates were selected for all studies: 0.1°C/min (slow rate) and 5.5°C/min (fast rate). Blends were crystallized in two conditions: (i) with agitation in an 80-mL crystallizer (dynamic), and (ii) on a microscope slide without agitation (static). The selected crystallization temperatures were 25, 30, and 35°C for both cooling rates. Photographs of the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 9 publications
4
35
0
Order By: Relevance
“…Higher agitation rate had a dramatic effect on crystal size resulting in formation of many small crystals (Herrera & Hartel, 2000), which is perhaps evidence of secondary nucleation caused by crystal contact mechanism (Hartel, 2001). Martini, Herrera & Hartel (2002) reported that blends of a high milk fat fraction and sunflower oil crystallised without agitation appeared to be more densely arranged within the crystal and to have bigger crystal sizes than samples crystallized in dynamic conditions. Breitschuh & Windhab (1996) showed that higher agitation promotes co-crystallization, probably due to an enhanced heat transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Higher agitation rate had a dramatic effect on crystal size resulting in formation of many small crystals (Herrera & Hartel, 2000), which is perhaps evidence of secondary nucleation caused by crystal contact mechanism (Hartel, 2001). Martini, Herrera & Hartel (2002) reported that blends of a high milk fat fraction and sunflower oil crystallised without agitation appeared to be more densely arranged within the crystal and to have bigger crystal sizes than samples crystallized in dynamic conditions. Breitschuh & Windhab (1996) showed that higher agitation promotes co-crystallization, probably due to an enhanced heat transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Besides fat composition, AMF has good sensory attributes such as flavor and mouthfeel [9]. To explore the different functional properties of AMF and its possible use in different food products such as spreads, dressings and shortenings, several authors have studied the effect of processing conditions and the addition of emulsifiers on the crystallization behavior of AMF and AMF fractions [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…They are not single crystals but clusters that grew by the accumulation of needles. A similar growth behavior was described for other fat systems (12). Therefore, no conclusion about the number of nuclei can be obtained from these images.…”
mentioning
confidence: 62%